The impact of network connectivity on factor exposures, asset pricing and portfolio diversification - Monica Billio; Massimiliano Caporin; Roberto Calogero Panzica; Loriana Pelizzon (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2017)
This paper extends the classic factor-based asset pricing model by including network linkages in linear factor models. We assume that the network linkages are exogenously provided. This extension of the model allows a better understanding of the causes of systematic risk and shows that (i) network exposures act as an inflating factor for systematic exposure to common factors and (ii) the power of diversification is reduced by the presence of network connections. Moreover, we show that in the presence of network links a misspecified traditional linear factor model presents residuals that are correlated and heteroskedastic. We support our claims with an extensive simulation experiment.
urn:nbn:de:hebis:30:3-428360
Keywords: G10; G12; F35; C58; 330; CAPM; volatility; network; interconnections; systematic risk